Electro-optic properties of a side chain poly(norbornene-dicarboximide) system with an appended phenyl vinylene thiophene chromophore. (16th June 2017) - Spring, Andrew M.; Qiu, Feng; Hong, Jianxun; Bannaron, Alisa; Yokoyama, Shiyoshi
Abstract: A side chain EO copolymer series has been synthesized by ROMP using the Grubbs 3rd generation initiator and quenched with ethyl vinyl ether. The copolymers were prepared by combining two norbornene-dicarboximide monomers, one with a cyclohexyl substituent and another substituted with an FTC chromophore. The mol% of the chromophore-substituted monomer was varied from 0.00 mol% to 22.92 mol%, all polymers were obtained in a yield of between 83 and 92% and a purity of between 97 and 98%. The cis : trans vinylene ratio remained constant at 1:1, confirming the polymers were amorphous. Peak molecular weights increased from 29, 541 g/mol to 142, 113 g/mol and the PDI increased from 1.36 to 4.01 respectively. Glass transition and thermal decomposition temperatures decreased from 206 °C to 168 °C and 433 °C to 382 °C as the mol% of the chromophore-substituted monomer was increased. UV–vis absorbance spectroscopy was used to quantify the chromophore content. A close correlation (68–95%) between the measured and calculated absorbance was found. The polymer containing 22.92 mol% of the chromophore-substituted monomer had a maximum r33 of 70 pm/V when polled at an optimum field of 60 V/μm at a polling temperature of 200 °C. This equates to a high polling efficiency of 1.16. High current flow in this polymer film at elevated field strength caused a breakdown of the electrode, preventing access to an elevated electro-optic coefficient. This polymer was found to have an excellent stability of 76% when aged at 85 °C for 1000 h in air. Graphical abstract: Highlights: Pre-polymerization chromophore functionalized EO material. Side chain EO copolymer series by ROMP. NDI monomer with an appended FTC chromophore. High polling efficiency material with an excellent thermal and temporal stability.